The Concept of Total Quality Management in Managing Educational Institutions - Fakhriy Falah; Anis Zohriah; Rijal Firdaus (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
A thought in a management system is related to the thought of an integrated quality management system in a quality management or total quality management (TQM). This management can create effectiveness and high quality. The quality of a service that is made for efficiency in terms of financing and efficient service as possible. This management requires a reference to become an alternative in creating customer satisfaction guarantees. Total Quality Management can also help a structural division to improve quality, with this all continuous efforts get attention to become more qualified. Total Quality Management is an application approach in integrating all functions and processes in an organization in order to improve the quality of goods and services together. This management concept directs the way to create an innovation in order to present customer satisfaction. Innovation and improvement in service must be interconnected. A purpose of this discussion is to analyze in aspects; 1). History of Total Quality Management; 2). Definition of Total Quality Management; 3). Quality of Total Quality Management; and 4). Elements in Total Quality Management. This discussion gets the result that the concept of Total Quality Management is an effort to improve quality dynamically in terms of products, services, which can meet customer expectations.